Synthesis of urea impregnated ruber wood biochar for retention of nitrogenoues nutrient in soil - Se, Sian Meng (2015)
Urea is one of the nitrogen sources for plants to grow. Upon its application to soil, mineralisation takes place, where urea [(NH2)2CO] is hydrolysed and converted to an intermediate compound known as ammonium carbonate [(NH4)2CO3]. Subsequently, it is converted to ammonium ions (NH4+) by urease activities for plant uptake. The remaining hydroxide ions (OH-) increase the soil's pH and release ammonia (NH3), a greenhouse gas produced after the reaction with NH4+. Some portions of NH4+ will be oxidised by oxygen in the air and converted to nitrite (NO2-) and nitrate (NO3-) by bacteria. The mobility of NO3- causes leaching by the run-off of ground water and surface water that leads to eutrophication. Many efforts have been carried out to address this matter. However, there are still some research gaps and room for improvement. Biochar derived from rubber wood sawdust (RWSD) is introduced to be impregnated with urea to slow down the mineralisation and reduce nitrogen losses. The main objective of this research is impregnation of urea onto biochar for nitrogenous nutrient retention in soil. The characterisation of biochars focused on physiochemical characteristics such as X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) surface area analysis, Fourier transform infrared (FT-IR) spectroscopy, Boehm titration, pH alkalinity, scanning electron microscopy (SEM) and SEM with energy-dispersive X-ray (SEM-EDX) spectroscopy. The porosities and acidic functional groups such as carboxylic (--COOH) groups are hypothesised to enhance the physio-chemi adsorption of urea onto biochar. The impregnation of urea onto biochar is performed by urea dissolution and recrystallisation with biochars content ranging from 2 % to 15 %. The ammonium and nitrate retained in soil after four weeks incubation are analysed by the first order kinetic model. It is observed that the mineralisation rate constant of urea is 54.4 %/week, higher compared with that of the impregnated samples at 5 % biochar obtained at 300 ºC, which is 25.9 %/week and urea impregnated biochar sample produced at 700 ºC with 10 % of impregnation, which is 28.9 %/week. In addition, the result from the total nitrogenous nutrient retention show that the percentage of biochar produced at 300 ºC ranging from 3 % to 7 % and those at 700 ºC ranging from 2 to 10 % are able to retain 15 % more nitrogenous compound than pristine urea. Moreover, ammonia volatilisation also indicated significant reduction after impregnation with the biochars with percentage ranging from 4 to 10 %, and exhibited the maximum ammonia loss of 35 % at 7.5 % of biochar. The reduction of ammonia emission is due to better nitrogen retention in soil upon impregnation. In addition, the trend nitrogenous nutrient retention in soil shows inverse quadratic relationship for both biochar while the ammonia emission shows a normal quadratic relationship. Hence, the emission of nitrous oxide is reported very minimal compared to pristine urea. Finally, the water column analysis revealed that the influence of urea impregnation with urea is negligible for ammonium. Nevertheless, the leaching of nitrate declined in the urea impregnated biochar sample due to the biochar contribution in reducing the mobility of nitrate in soil.